Self-excited geopolymer anti-corrosion coating and preparation method thereof

By growing DTPMP calcium-molecule hydrotalcite in fly ash hollow microbeads and forming a ternary alkaline environment, the problem of complex and strong alkaline exciters of hydrotalcite synthesis is solved, and the corrosion resistance and hardness of geopolymer coatings are improved. The construction process is simplified and the corrosion protection and cost-effective effect is achieved.

CN119161753AActive Publication Date: 2024-12-20FUZHOU UNIV

Patent Information

Application Number
CN202411507337.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2024-12-20
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

The durability of existing poly anti-corrosion coatings in coastal environments is threatened by corrosive chemicals. Hydrtal synthesis is complex and costly. Strong alkaline excitants lead to rapid condensation and construction difficulty, and the environment and Inconvenient transportation.

Method used

Fly ash hollow microbeads are used as hydrotalcite carriers, and calcium-molecule hydrotalcite with DTPMP loading is grown inside through microwave assisted technology, combining activated red mud powder, calcium carbide slag powder, and wood ash powder to form a ternary alkaline environment to stimulate silicoaluminoic acid Salt reaction reduces early self-shrinkage and improves corrosion resistance of the coating.

Benefits of technology

It effectively avoids hydrotalcite agglomeration and early replacement reactions, improves the corrosion resistance and hardness of the coating, simplifies the construction process, reduces environmental pollution and construction difficulty, and the materials are derived from industrial solid waste, which is environmentally friendly and cost-effective.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a self-excited geopolymer anti-corrosion coating and a preparation method thereof. The self-excited geopolymer anti-corrosion coating is prepared from modified fly ash hollow microspheres, superfine slag powder, recycled concrete micro powder, desulfurized gypsum, activated red mud powder, carbide slag powder, plant ash powder, a polycarboxylate superplasticizer, a defoaming agent and the like. The modified fly ash hollow microspheres are modified calcium-iron hydrotalcite coated with fly ash hollow microspheres. The DTPMP-loaded calcium-iron hydrotalcite is grown in situ in the acidized fly ash hollow microspheres by utilizing a microwave-assisted technology, so that the harmful ion replacement effect of the geopolymer anti-corrosion coating can be improved, and the corrosion resistance of the geopolymer anti-corrosion coating can be improved; meanwhile, the modified red mud powder, the carbide slag powder and the plant ash powder can form a ternary alkaline environment rich in Ca (OH), Na (OH) and Ka (OH) when encountering water, and an aluminosilicate precursor is excited to carry out a more sufficient geopolymerization reaction, so that the self-excited geopolymer anti-corrosion coating which is firm, compact and high in chloride ion permeability resistance is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of geopolymer-based anticorrosion coatings, and in particular relates to a self-excited geopolymer anticorrosion coating and a preparation method thereof, and is intended to effectively protect reinforced concrete structures in coastal environments. Background Art

[0002] Reinforced concrete structures are a widely used form of engineering structure in the world. However, when the structure is corroded by corrosive chemicals such as chloride ions, sulfate ions and carbonate ions, its durability will be seriously threatened. Especially in coastal environments, the high concentration of corrosive ions (especially chloride ions) in seawater greatly exacerbates this corrosion phenomenon. A large number of corrosive ions penetrate into the surface of the steel bars through the pore structure inside the concrete and destroy the self-repairing passivation layer on the surface of the steel bars, thus causing corrosion of the steel bars, further causing damage and failure of the reinforced concrete structure.

[0003] Geopolymer is an inorganic polymer that is generated by the excitation reaction of aluminosilicate materials under alkaline conditions. Its special three-dimensional network structure comes from the dissolution and re-condensation process of aluminosilicate. The inherent durability of this structure and its good adhesion to cement-based materials and building steel make geopolymer an ideal surface corrosion protection coating. Its anti-corrosion mechanism mainly relies on the reaction of CASH and CSH to Cl - Physical adsorption of Cl - Chemical adsorption. Due to its unique two-dimensional structure, hydrotalcite has good anion replacement ability. Therefore, many researchers have added hydrotalcite to anti-corrosion coatings to improve the coating's adsorption capacity for harmful chloride ions, thereby improving the corrosion resistance of the coating in harsh environments. However, due to the strong van der Waals force interaction between hydrotalcites, directly adding hydrotalcite to the coating can easily cause the hydrotalcite powder to agglomerate. At the same time, due to the strong ion replacement ability of hydrotalcite, in the early stage of the hydration reaction of the geopolymer coating, hydrotalcite is easy to react with the free Cl inside the geopolymer. - 、SO4 2- 、CO3 2- The replacement reaction occurs in advance, resulting in a significant weakening of the ion replacement ability of hydrotalcite after the geopolymer coating is hardened. In addition, hydrotalcite is mostly synthesized by traditional hydrothermal method, which is time-consuming and has strict requirements on the synthesis temperature. The steps are complicated and the cost is high, which is not conducive to large-scale synthesis.

[0004] At present, commonly used geopolymer activators, such as sodium silicate, sodium hydroxide and other strong alkaline chemicals, can quickly promote the dissolution of aluminosilicate into silicon-oxygen tetrahedron SiO4 4- and aluminum oxide tetrahedron AlO45- , and then these compounds re-condense and harden. This process easily leads to the rapid setting of the geopolymer slurry, which limits the ease of use and construction time of the coating, and the coating has a large self-shrinkage in the early stage, and is prone to cracking during the hardening process. In addition, these strong alkaline activators usually need to be pre-prepared in a specific proportion, which increases the difficulty of construction, and are corrosive to a certain extent, making long-term storage and transportation inconvenient. Therefore, more and more scholars are committed to studying a method that only requires the addition of water and relies on the alkaline environment formed by the cementitious material when it meets water to carry out geopolymerization. However, the alkaline environment formed by industrial solid waste has the problems of low strength, large early self-shrinkage, and resistance to Cl in actual use. - Poor permeability and other issues. Summary of the invention

[0005] In order to solve the problems existing in the prior art, the present invention provides a self-excited geopolymer anti-corrosion coating and a preparation method thereof.

[0006] To achieve the above object, the present invention adopts the following technical solution: A self-excited geopolymer anti-corrosion coating, the raw materials used for which include, by weight: 20-30 parts of modified fly ash hollow microspheres, 30-40 parts of ultrafine slag powder, 20-30 parts of recycled concrete powder, 10-20 parts of desulfurized gypsum, 5-10 parts of activated red mud powder, 10-20 parts of carbide slag powder, 5-10 parts of wood ash powder, 0.2-0.3 parts of polycarboxylic acid water reducer, 0.3-0.5 parts of defoaming agent, and 50-60 parts of deionized water.

[0007] Furthermore, the modified fly ash hollow microspheres are specifically fly ash hollow microspheres coated with modified calcium iron hydrotalcite; the preparation thereof comprises the following steps: 1) Add fly ash hollow microspheres into deionized water at a solid-liquid ratio of 1g:10mL, adjust the pH value to 1.5-2, stir at room temperature for 2h, filter, wash with deionized water for 3 times, put into a drying oven at 60℃, and dry for 4h to obtain pretreated fly ash hollow microspheres; 2) Add the fly ash hollow microspheres pretreated in step 1) into deionized water at a solid-liquid ratio of 1g:10mL, add calcium nitrate hexahydrate (Ca(NO3)2·6H2O), ferric nitrate nonahydrate (Fe(NO3)2·9H2O), and diethylenetriaminepenta(methylenephosphonic acid) (DTPMP) after ultrasonic dispersion, adjust the pH value to 10-11, keep warm at 46-50°C and stir for 2h, then transfer to a vacuum box and place for 1h to obtain a suspension; 3) The suspension obtained in step 2) was subjected to microwave treatment, and after cooling to room temperature, the suspension was filtered, washed with deionized water for 3 times, and then transferred to a 60° C. vacuum drying oven and dried for 8 h to obtain fly ash hollow microspheres coated with modified calcium iron hydrotalcite.

[0008] Furthermore, the frequency of the ultrasonic dispersion in step 2) is 20-40 KHz, and the time is 8-15 min.

[0009] Furthermore, the mass ratio of the pretreated fly ash hollow microspheres, calcium nitrate hexahydrate, ferric nitrate nonahydrate and DTPMP used in step 2) is 5:1.2:1.1:0.8.

[0010] Furthermore, the microwave treatment in step 3) is performed at a temperature of 85-90° C., a power of 450 W, and a time of 30 min.

[0011] Furthermore, the activated red mud powder is prepared by placing the red mud powder in a muffle furnace and calcining it at 700° C. for 4 hours (heating rate of 5° C. / min).

[0012] The fly ash hollow microspheres used above are 80-120 mesh. The ultrafine slag powder used is 300-400 mesh. The recycled concrete powder used is 100-200 mesh. The desulfurized gypsum used is 100-200 mesh. The calcium carbide slag powder used is 200-300 mesh. The plant ash powder used is 200-300 mesh. The red mud powder used is 200-300 mesh.

[0013] The preparation method of the self-excited geopolymer anti-corrosion coating is as follows: modified fly ash hollow microspheres, ultrafine slag powder, recycled concrete powder, desulfurized gypsum, activated red mud powder, carbide slag powder, wood ash powder, defoamer, and polycarboxylic acid water reducer are dry-mixed in proportion, with the dry-mixing speed being 150-200 r / min; then, deionized water is added and stirring is continued for 3-4 minutes, with the stirring speed being 1500-1800 r / min, to obtain the self-excited geopolymer anti-corrosion coating.

[0014] The present invention uses microwave-assisted technology to in-situ grow DTPMP-loaded calcium iron hydrotalcite inside acidified fly ash hollow microspheres, and uses the hydrotalcite in geopolymer anti-corrosion coatings, thereby improving the effect of replacing harmful ions in the geopolymer anti-corrosion coatings and improving their corrosion resistance. At the same time, activated red mud powder, carbide slag powder, and plant ash powder can form a ternary alkaline environment rich in Ca(OH), Na(OH), and Ka(OH) when in contact with water, thereby stimulating aluminosilicate precursors to perform more sufficient geopolymerization reactions. The filling effect of recycled concrete micropowder and fly ash hollow microspheres is also utilized to reduce the self-shrinkage rate of early self-excited geopolymers, thereby preventing harmful substances from directly corroding the substrate through cracks.

[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention uses fly ash hollow microspheres as the carrier of hydrotalcite. The good dispersibility of fly ash hollow microspheres can avoid the agglomeration of hydrotalcite in geopolymer anti-corrosion coatings. At the same time, under the coating of fly ash hollow microspheres, the Cl - 、SO4 2- 、CO3 2- The replacement reaction takes place in advance, which effectively ensures that the geopolymer anti-corrosion coating replaces Cl after hardening. - 、SO4 2- The ability to remove harmful ions.

[0016] 2. The present invention utilizes microwave-assisted technology to in-situ grow calcium iron hydrotalcite loaded with corrosion inhibitor DTPMP inside the acidified fly ash hollow microspheres. It utilizes electromagnetic waves to directly interact with ions in the solution, with high heating rate and uniform heating, effectively improving the problems of long time consumption, complex technology, and high cost in the traditional hydrothermal method of synthesizing hydrotalcite, and is helpful for the rapid synthesis of hydrotalcite nanocrystals with smaller and more uniform particle sizes, greatly improving the synthesis rate of hydrotalcite. At the same time, DTPMP, as an organic phosphonate compound, is a green corrosion inhibitor, and its phosphonic acid group has a strong affinity for the steel surface, and can form a two-dimensional monomolecular phosphonate film layer on the steel surface by chemical or physical adsorption, thereby blocking the erosion of the corrosive medium. The loaded DTPMP in the present invention can be released during use, showing good corrosion protection ability, thereby improving the corrosion resistance of the geopolymer anti-corrosion coating.

[0017] 3. The activated red mud powder, carbide slag powder and plant ash powder in the present invention form a ternary alkaline environment rich in Ca(OH), Na(OH) and Ka(OH) when in contact with water, which can effectively accelerate the dissolution and re-condensation of aluminosilicate precursors, produce more CASH, CSH and NASH gels, thereby improving the hardness of the self-excited geopolymer coating and forming a dense and solid protective layer. At the same time, due to the filling effect of recycled concrete micropowder and fly ash hollow microspheres, the self-shrinkage rate of the early self-excited geopolymer is reduced, preventing harmful substances from directly corroding the substrate through cracks.

[0018] 4. The cementitious material of the present invention is derived from industrial solid waste, construction solid waste, and biomass combustion ash. It adopts an environmentally friendly and cost-effective production method. No alkaline activator is required. Hardening can be completed by simply adding water and mixing. This greatly simplifies the construction process and is conducive to long-term storage and transportation of materials. At the same time, the present invention reduces environmental pollution and avoids potential harm to construction workers caused by strong alkali during the construction process, further reflecting the advantages of green environmental protection. DETAILED DESCRIPTION

[0019] A self-excited geopolymer anti-corrosion coating, the raw materials used for which include, by weight: 20-30 parts of modified fly ash hollow microspheres, 30-40 parts of ultrafine slag powder, 20-30 parts of recycled concrete powder, 10-20 parts of desulfurized gypsum, 5-10 parts of activated red mud powder, 10-20 parts of carbide slag powder, 5-10 parts of wood ash powder, 0.2-0.3 parts of polycarboxylic acid water reducer, 0.3-0.5 parts of defoaming agent, and 50-60 parts of deionized water.

[0020] The preparation method of the self-excited geopolymer anti-corrosion coating comprises the following steps: 1) Add fly ash hollow microspheres into deionized water at a solid-liquid ratio of 1g:10mL, add 0.1mol / L hydrochloric acid solution to adjust the pH value to 1.5-2, stir at room temperature for 2h, filter, wash with deionized water for 3 times, put into a drying oven at 60℃, and dry for 4h to obtain pretreated fly ash hollow microspheres; 2) Add the fly ash hollow microspheres pretreated in step 1) to deionized water at a solid-liquid ratio of 1g:10mL, and ultrasonically disperse them at a frequency of 20-40KHz for 8-15min. Then, add calcium nitrate hexahydrate (Ca(NO3)2·6H2O), ferric nitrate nonahydrate (Fe(NO3)2·9H2O), and diethylenetriamine penta (methylenephosphonic acid) (DTPMP) at a mass ratio of 5:1.2:1.1:0.8, add 0.1mol / L sodium hydroxide solution to adjust the pH value to 10-11, and stir at 46-50℃ for 2h (heating rate of 6.0-6.8℃ / min), then transfer to a vacuum box and place for 1h to obtain a suspension; 3) The suspension obtained in step 2) is subjected to microwave treatment at 85-90° C. and 450 W power for 30 min, and after cooling to room temperature, the suspension is filtered, washed with deionized water for 3 times, and then transferred to a 60° C. vacuum drying oven and dried for 8 h to obtain fly ash hollow microspheres coated with modified calcium iron hydrotalcite, i.e., modified fly ash hollow microspheres; 4) placing the red mud powder in a muffle furnace and calcining at 700°C for 4 hours (heating rate of 5°C / min) to obtain activated red mud powder; 5) Dry-mix the modified fly ash hollow microspheres, ultrafine slag powder, recycled concrete powder, desulfurized gypsum, activated red mud powder, carbide slag powder, wood ash powder, defoamer, and polycarboxylic acid water reducer in proportion at a dry mixing speed of 150-200 r / min; then, add deionized water and continue stirring for 3-4 minutes at a stirring speed of 1500-1800 r / min to obtain a self-excited geopolymer anti-corrosion coating.

[0021] The present invention provides a self-excited geopolymer anti-corrosion coating and a preparation method thereof. To further illustrate the technical means and effects adopted by the present invention, the present invention is described in detail below in conjunction with specific implementation methods.

[0022] The fly ash hollow microspheres used are 80~120 meshes; the ultrafine slag powder is 300~400 meshes; the recycled concrete micropowder is 100~200 meshes; the desulfurized gypsum is 100~200 meshes; the carbide slag powder is 200~300 meshes; the wood ash powder is 200~300 meshes; and the red mud powder is 200~300 meshes. Example

[0023] In this embodiment, the raw material ratio of the self-excited geopolymer anti-corrosion coating is, by weight: 22 parts of modified fly ash hollow microspheres, 28 parts of recycled concrete powder, 35 parts of ultrafine slag powder, 15 parts of desulfurized gypsum, 10 parts of activated red mud powder, 15 parts of calcium carbide slag powder, 5 parts of wood ash powder, 0.2 parts of polycarboxylic acid water reducer, 0.4 parts of defoaming agent, and 60 parts of deionized water.

[0024] In this embodiment, the preparation method of the self-excited geopolymer anti-corrosion coating is carried out according to the following steps: Step 1: Add fly ash hollow microspheres into deionized water at a solid-liquid ratio of 1g:10mL, add 0.1mol / L hydrochloric acid solution to adjust the pH value to 1.5-2, stir at room temperature for 2h, filter, wash with deionized water 3 times, put in a 60℃ drying oven, and dry for 4h; Step 2: Add the fly ash hollow microspheres dried in step 1 to deionized water at a solid-liquid ratio of 1g:10mL, and ultrasonically disperse at a frequency of 20-40KHz for 8-15min, then add Ca(NO3)2·6H2O, Fe(NO3)2·9H2O, and DTPMP at a mass ratio of 5:1.2:1.1:0.8, add 0.1mol / L sodium hydroxide solution to adjust the pH value to 10-11, keep warm and stir at 46-50℃ for 2h (heating rate of 6.0-6.8℃ / min), then transfer to a vacuum box and place for 1h to obtain a suspension; Step 3: subjecting the suspension obtained in step 2 to microwave treatment, with a microwave power of 450W, a temperature of 85-90°C, and a treatment time of 30min. After cooling to room temperature, the suspension is filtered, washed with deionized water for 3 times, and then transferred to a 60°C vacuum drying oven for drying for 8h to obtain fly ash hollow microspheres coated with modified calcium iron hydrotalcite, i.e., modified fly ash hollow microspheres; Step 4: placing the red mud powder in a muffle furnace for calcination at a temperature of 700°C (heating rate of 5°C / min) for 4 hours to obtain activated red mud powder; Step 5: dry-mix the modified fly ash hollow microspheres, ultrafine slag powder, recycled concrete powder, activated red mud powder, desulfurized gypsum, carbide slag powder, wood ash powder, defoamer and polycarboxylic acid water reducer in proportion, with the dry-mixing speed being 150-200 r / min; then, add deionized water and continue stirring for 3-4 minutes, with the stirring speed being 1500-1800 r / min, to obtain a self-excited geopolymer anti-corrosion coating.

[0025] Comparative Example 1: No modification of fly ash hollow microspheres In this embodiment, the raw material ratio of the self-excited geopolymer coating is as follows, by weight: 12 parts of fly ash hollow microspheres, 10 parts of DTPMP modified calcium iron hydrotalcite, 28 parts of recycled concrete powder, 35 parts of ultrafine slag powder, 15 parts of desulfurized gypsum, 10 parts of activated red mud powder, 15 parts of calcium carbide slag powder, 5 parts of wood ash powder, 0.2 parts of polycarboxylic acid water reducer, 0.4 parts of defoaming agent, and 60 parts of deionized water.

[0026] In this embodiment, the preparation method of the self-excited geopolymer coating is carried out according to the following steps: Step 1: Mix Ca(NO3)2·6H2O, Fe(NO3)2·9H2O and DTPMP in a mass ratio of 1.2:1.1:0.8, then add them into deionized water in a solid-liquid ratio of 1g:10mL, add 0.1mol / L sodium hydroxide solution to adjust the pH value to 10-11, and stir at 46-50℃ for 2h (heating rate of 6.0-6.8℃ / min) to obtain a suspension; Step 2: subjecting the suspension obtained in step 1 to microwave treatment, with a microwave power of 450 W, a temperature of 85-90 ° C, and a treatment time of 30 min. After cooling to room temperature, the suspension is filtered, washed with deionized water for 3 times, and then transferred to a 60 ° C vacuum drying oven for drying for 8 h to obtain DTPMP-modified calcium iron hydrotalcite; Step 3: Place the red mud powder in a muffle furnace for calcination at a temperature of 700°C (heating rate of 5°C / min) for 4 hours to obtain activated red mud powder.

[0027] Step 4: dry-mix fly ash hollow microspheres, ultrafine slag powder, recycled concrete powder, desulfurized gypsum, activated red mud powder, carbide slag powder, plant ash powder, DTPMP modified calcium iron hydrotalcite, defoamer, and polycarboxylate water reducer in proportion, with a dry-mixing speed of 150-200 r / min; then, add deionized water and continue stirring for 3-4 minutes, with a stirring speed of 1500-1800 r / min. Thus, a self-excited geopolymer coating is obtained.

[0028] Comparative Example 2 does not use microwave technology In this embodiment, the raw material ratio of the self-excited geopolymer coating is, by weight: 22 parts of modified fly ash hollow microspheres, 28 parts of recycled concrete powder, 35 parts of ultrafine slag powder, 15 parts of desulfurized gypsum, 10 parts of activated red mud powder, 15 parts of calcium carbide slag powder, 5 parts of wood ash powder, 0.2 parts of polycarboxylic acid water reducer, 0.4 parts of defoaming agent, and 60 parts of deionized water.

[0029] In this embodiment, the preparation method of the self-excited geopolymer coating is carried out according to the following steps: Step 1: Add fly ash hollow microspheres into deionized water at a solid-liquid ratio of 1g:10mL, add 0.1mol / L hydrochloric acid solution to adjust the pH value to 1.5-2, stir at room temperature for 2h, filter, wash with deionized water 3 times, put in a 60℃ drying oven, and dry for 4h; Step 2: Add the dried fly ash hollow microspheres obtained in step 1 to deionized water at a solid-liquid ratio of 1g:10mL, and ultrasonically disperse them at a frequency of 20~40KHz for 8~15min. Then, add Ca(NO3)2·6H2O, Fe(NO3)2·9H2O, and DTPMP at a mass ratio of 5:1.2:1.1:0.8, add 0.1mol / L sodium hydroxide solution to adjust the pH value to 10-11, and stir at 46~50℃ for 2h (heating rate of 6.0~6.8℃ / min), cool to room temperature, filter, wash with deionized water 3 times, and then transfer to a 60℃ vacuum drying oven and dry for 8h to obtain modified fly ash hollow microspheres without microwave treatment.

[0030] Step 3: placing the red mud powder in a muffle furnace for calcination at a temperature of 700°C (heating rate of 5°C / min) for 4 hours to obtain activated red mud powder; Step 4: dry-mix the modified fly ash hollow microspheres, ultrafine slag powder, recycled concrete powder, activated red mud powder, desulfurized gypsum, carbide slag powder, wood ash powder, defoamer and polycarboxylic acid water reducer in proportion, with the dry-mixing speed being 150-200 r / min; then, add deionized water and continue stirring for 3-4 minutes, with the stirring speed being 1500-1800 r / min, to obtain a self-excited geopolymer coating.

[0031] Comparative Example 3: No DTPMP added In this embodiment, the raw material ratio of the self-excited geopolymer coating is, by weight: 22 parts of modified fly ash hollow microspheres, 28 parts of recycled concrete powder, 35 parts of ultrafine slag powder, 15 parts of desulfurized gypsum, 10 parts of activated red mud powder, 15 parts of calcium carbide slag powder, 5 parts of wood ash powder, 0.2 parts of polycarboxylic acid water reducer, 0.4 parts of defoaming agent, and 60 parts of deionized water.

[0032] In this embodiment, the preparation method of the self-excited geopolymer coating is carried out according to the following steps: Step 1: Add fly ash hollow microspheres into deionized water at a solid-liquid ratio of 1g:10mL, add 0.1mol / L hydrochloric acid solution to adjust the pH value to 1.5-2, stir at room temperature for 2h, filter, wash with deionized water 3 times, put in a 60℃ drying oven, and dry for 4h; Step 2: Add the dried fly ash hollow microspheres obtained in step 1 to deionized water at a solid-liquid ratio of 1g:10mL, and ultrasonically disperse them at a frequency of 20-40KHz for 8-15min, then add Ca(NO3)2·6H2O and Fe(NO3)2·9H2O at a mass ratio of 5:1.2:1.1, add 0.1mol / L sodium hydroxide solution to adjust the pH value to 10-11, and stir at 46-50℃ for 2h (heating rate of 6.0-6.8℃ / min), then transfer to a vacuum box and place for 1h to obtain a suspension; Step 3: subjecting the suspension obtained in step 2 to microwave treatment, with a microwave power of 450W, a temperature of 85-90°C, and a treatment time of 30min. After cooling to room temperature, the suspension is filtered, washed with deionized water for 3 times, and then transferred to a 60°C vacuum drying oven for drying for 8h to obtain modified fly ash hollow microspheres; Step 4: placing the red mud powder in a muffle furnace for calcination at a temperature of 700°C (heating rate of 5°C / min) for 4 hours to obtain activated red mud powder; Step 5: dry-mix the modified fly ash hollow microspheres, ultrafine slag powder, recycled concrete powder, desulfurized gypsum, modified red mud powder, carbide slag, wood ash, defoamer and polycarboxylic acid water reducer in proportion, with the dry-mixing speed being 150-200 r / min; then, add deionized water and continue stirring for 3-4 minutes, with the stirring speed being 1500-1800 r / min, to obtain a self-excited geopolymer coating.

[0033] The corrosion resistance of the coating was determined in the following manner, and the results are shown in Table 1: (1) Spray or dip the coating evenly on the steel bar surface. Curing for 7 days at a temperature of 20°C and a humidity of 60-70%. Place the coated steel bar in simulated seawater for accelerated corrosion with an applied voltage of 26V and a corrosion time of 1 hour. After the corrosion is completed, the corrosion current density and rust resistance of the coated steel bar are tested using an electrochemical workstation.

[0034] Rust resistance rate ( or ) Calculation formula: , Among them, I corr,0 is the current density of uncoated steel bars, I corr is the current density of coated steel bar.

[0035] (2) The coating is evenly applied on the surface of the concrete test block by spraying or brushing. The thickness of the coating is 1±0.1mm. The size of the concrete test block is 100mm in diameter and 50mm in height. After curing for one week at a temperature of 20℃ and a humidity of 95%, the concrete test block coated with the coating is subjected to a rapid chloride ion penetration performance test in accordance with the national standard GB / T50082-2024 "Standard for Test Methods for Long-term Performance and Durability of Concrete".

[0036] (3) After curing the paint at a temperature of 20°C and a humidity of 95% for 7 days, the paint was crushed and dried, and sieved with a 100-mesh screen to obtain a paint dry powder. The paint dry powder was added to a 0.1 mol / L sodium chloride solution at a solid-liquid ratio of 1g:5ml, and chloride ion adsorption was performed at a temperature of 20°C. After 7 days, the chloride ion content of the obtained filtrate was tested.

[0037] Table 1

[0038] As can be seen from the results in Table 1, the rust resistance rate of the steel bars coated in the embodiment reaches 97.5%, which is significantly higher than that in the comparative embodiment, indicating that the coating prepared in the embodiment can provide better corrosion protection for the steel bars. At the same time, the chloride ion penetration depth in the embodiment is only 0.5 mm, while the chloride ion penetration depth in the comparative embodiment is >1.8 mm, indicating that the coating in the embodiment can completely fix the chloride ions inside the coating, and thus has better resistance to chloride ion penetration. The chloride ion adsorption amount of the coating dry powder in the embodiment is 5.83 mg / g, showing an excellent chloride ion adsorption level.

[0039] The above is only a preferred embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any equivalent changes and modifications made by any technician familiar with the technical field within the technical scope disclosed by the present invention and in accordance with the scope of the patent application of the present invention shall fall within the scope of the present invention.

Claims

1. A self-excited geopolymer anti-corrosion coating, characterized in that: The raw materials used include, by weight: 20-30 parts of modified fly ash hollow microspheres, 30-40 parts of ultrafine slag powder, 20-30 parts of recycled concrete powder, 10-20 parts of desulfurized gypsum, 5-10 parts of activated red mud powder, 10-20 parts of carbide slag powder, 5-10 parts of plant ash powder, 0.2-0.3 parts of polycarboxylic acid water reducer, 0.3-0.5 parts of defoamer, and 50-60 parts of deionized water; The modified fly ash hollow microspheres are specifically modified calcium iron hydrotalcite coated with fly ash hollow microspheres.

2. The self-excited geopolymer anti-corrosion coating according to claim 1, characterized in that: The preparation of the modified fly ash hollow microspheres comprises the following steps: 1) Add fly ash hollow microspheres into deionized water at a solid-liquid ratio of 1g:10mL, adjust the pH value to 1.5-2, stir at room temperature for 2h, filter, wash with deionized water for 3 times, and dry at 60℃ for 4h to obtain pretreated fly ash hollow microspheres; 2) Add the fly ash hollow microspheres pretreated in step 1) into deionized water at a solid-liquid ratio of 1g:10mL, add calcium nitrate hexahydrate, ferric nitrate nonahydrate, and diethylenetriamine penta (methylene phosphonic acid) after ultrasonic dispersion, adjust the pH value to 10-11, keep stirring at 46-50°C for 2h, and then transfer to a vacuum box for 1h to obtain a suspension; 3) The suspension obtained in step 2) is subjected to microwave treatment, then cooled at room temperature and filtered, washed with deionized water for three times, and then dried at 60° C. for 8 h to obtain fly ash hollow microspheres coated with modified calcium iron hydrotalcite.

3. The self-excited geopolymer anti-corrosion coating according to claim 2, characterized in that: The frequency of the ultrasonic dispersion in step 2) is 20-40 KHz, and the time is 8-15 min.

4. The self-excited geopolymer anti-corrosion coating according to claim 2, characterized in that: The mass ratio of the pretreated fly ash hollow microspheres, calcium nitrate hexahydrate, ferric nitrate nonahydrate and diethylenetriaminepenta(methylenephosphonic acid) used in step 2) is 5:1.2:1.1:0.

8.

5. The self-excited geopolymer anti-corrosion coating according to claim 2, characterized in that: The microwave treatment in step 3) is performed at a temperature of 85-90° C., a power of 450 W, and a time of 30 min.

6. The self-excited geopolymer anti-corrosion coating according to claim 1, characterized in that: The activated red mud powder is prepared by placing the red mud powder in a muffle furnace and calcining it at 700° C. for 4 hours.

7. A method for preparing the self-excited geopolymer anti-corrosion coating according to claim 1, characterized in that: Modified fly ash hollow microspheres, ultrafine slag powder, recycled concrete powder, desulfurized gypsum, activated red mud powder, carbide slag powder, wood ash powder, defoamer, and polycarboxylic acid water reducer are dry-mixed in proportion; then, deionized water is added and stirring is continued for 3 to 4 minutes to obtain the self-excited geopolymer anti-corrosion coating.

8. The method for preparing the self-excited geopolymer anti-corrosion coating according to claim 7, characterized in that: The rotation speed of the dry mixing is 150-200 r / min; the rotation speed of the stirring is 1500-1800 r / min.

Citation Information

Patent Citations

  • Light geopolymer material containing carbon nanotube modified hollow microspheres and preparation method thereof

    CN117164379A

  • Self-excited geopolymer concrete and preparation method thereof

    CN117510143A

  • Red mud-based sewage treatment agent, preparation method therefor, red mud-based ceramsite concrete, preparation method for same, and applications thereof

    WO2021168995A1

Cited By

  • Geopolymer alkali activator based on red mud raw material and preparation method thereof

    CN121063852A